2012
DOI: 10.1007/s11547-012-0903-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of quantitative elastography with supersonic shear imaging in the diagnosis of breast tumours

Abstract: Shear-wave elastography gives quantitative elasticity information that could potentially help in breast-lesion characterisation, although it cannot replace conventional BI-RADS in the differentiation of breast lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
28
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 17 publications
5
28
1
Order By: Relevance
“…Further, low-grade malignant lesions and benign lesions with sclerosing components tend to yield to false-negative and false-positive results, respectively. This shows that malignant and benign breast lesions exhibit overlapping features, as reported in previous studies (16,18,22,26).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Further, low-grade malignant lesions and benign lesions with sclerosing components tend to yield to false-negative and false-positive results, respectively. This shows that malignant and benign breast lesions exhibit overlapping features, as reported in previous studies (16,18,22,26).…”
Section: Discussionsupporting
confidence: 86%
“…SWE differs from conventional elastography in that the former technique yields quantitative data and appears to be more reproducible and objective (16). In the present work, the most useful and reproducible measure was the mass/fat elasticity ratio, unlike what was found by Wang et al (P < 0.01 vs. P = 0.088) (18). Breast fat tissue shows minimal elastographic variability, and the elasticity values are very low, supporting the use of fat tissue stiffness as a comparator (16,19).…”
Section: Discussioncontrasting
confidence: 52%
“…Other studies demonstrated that E max was the quantitative SWE feature of the optimal performance for breast cancer diagnosis733. In our study, E max showed remarkable performance, with an AUC of 0.943 in 2D SWE.…”
Section: Discussionsupporting
confidence: 64%
“…This observation is in good agreement with the results of a previously published study 24 . There are many studies focused on SWE diagnosis, but the Emax cutoff value, sensitivity and specificity were different 25, 26 . Berg et al .…”
Section: Discussionmentioning
confidence: 99%